Emerging Threats and Security Planning How Should We Decide What Hypothetical Threats to Worry About? - Jackson, Brian A. (RAND Corporation, 2009)
Concerns about how terrorists might attack in the future are central to the design of security efforts to protect both individual targets and the nation overall. This paper explores an approach for assessing novel or emerging threats and prioritizing which merit specific security attention and which can be addressed as part of existing security efforts.